Macroeconomy for development: Countercyclical policies and production sector transformation - José Antonio Ocampo (CEPAL Review, 2011)
The argument that I will be making here is that the key to a well-designed macroeconomic policy for development is a mix of sound countercyclical policies and a proactive strategy for diversifying production structures. These two concepts are deeply rooted in eclac thinking. Countercyclical policies must withstand the challenges posed by abrupt external financing cycles and sharp fluctuations in commodity prices. Fiscal policy is of pivotal importance, but it must be coupled with equally countercyclical monetary and exchange-rate policies. In the light of the experience over the past decade, this policy mix seems to be achievable if intermediate exchange regimes are introduced alongside macroprudential policies, including regulation of capital flows. At the same time, the strategy used to spur the development of the production sector should foster innovative economic activities that generate domestic production linkages. The concept of innovation must be understood in a broad sense, but the critical test is its contribution to the accumulation of technological capabilities.